Trend, challenges, and determinants of technology integration in geometry problems-solving: A sequential explanatory analysis - Maulidiya, Della; Aziza, Mela (Universitas Islam Negeri Raden Intan Lampung, 2024)
This study explores trends, challenges, and success factors in integrating technology to enhance students' conceptual understanding and problem-solving skills in geometry. Using a sequential explanatory design, a quantitative analysis based on text mining and bibliometric methods was conducted on 197 articles from the ERIC database, followed by thematic analysis. The results indicate an annual publication growth of 32.26%, with key success factors including teacher competence, students' mathematical literacy, pedagogy-technology integration, and evaluation of instructional effectiveness. The COVID-19 pandemic accelerated the transformation of technology from an auxiliary tool to a core element of active learning. However, limited access and technological adaptation to complex problems remain significant obstacles. This study recommends teacher training, exploration of technology in teaching, and the development of innovative strategies and accessible technological tools. The implications of this study provide strategic guidance for policymakers, educators, and developers to optimize the use of technology in geometry education more innovatively and inclusively.